Richir and the transcendental origin of the dissociative experience (Spaltung) - Zúñiga, Bryan (Estudios de Filosofía, 2024)
Phenomenology describes the transcendental structures of human experience within its constant relationship with the world. Moments such as affectivity, temporality, corporeality, spatiality, and intersubjectivity thus constitute key elements within this ap-proach. In this context, the following contribution aims to describe an experience of great importance in the works circumscribed in phenomenological psychopathology, namely, the experience of dissociation (Spaltung). To achieve this task, our article will have three moments. First, it will present a phenomenological description of the lived body (Leib). Second, considering Marc Richir’s philosophy, it will outline a genetic phenomenology that reveals the first constitution of the body schema during childhood through Phantasy’s labor. Finally, it will present a genetic phenomenology of the lived body that sheds light on the transcendental origin of the dissociative experience